DISTRIBUTION AND SHORT‐ AND LONG‐TERM EFFECTS OF INJECTED GELIFIED ETHANOL INTO THE LUMBOSACRAL INTERVERTEBRAL DISC IN HEALTHY DOGS. Issue 2 (2nd December 2015) - Mackenzie, Shawn D.; Brisson, Brigitte A.; Gaitero, Luis; Caswell, Jeff L.; Liao, Penting; Sinclair, Melissa; Chalmers, Heather J.
Abstract : Radiopaque gelified ethanol preparation has been described as a useful agent for treatment of humans with intervertebral disc protrusion. The material is injected into the nucleus pulposus under image guidance with intention to cause the protruded disc material to recede. Because treatment options for dogs with chronic protrusions are limited, new and minimally invasive treatments are desirable. The aim of this experimental, descriptive, prospective study was to assess the feasibility and safety of percutaneous injection of gelified ethanol into the lumbosacral intervertebral disc of dogs. Lumbosacral intervertebral discs of normal dogs ( n = 9) were imaged with magnetic resonance imaging and then injected with gelified ethanol using image guidance. The accuracy of gelified ethanol placement in the nucleus pulposus and presence of leakage of the injected material were documented. Postinjection computed tomography (CT) findings ( n = 9), short‐term ( n = 9) and long‐term ( n = 4) follow‐up magnetic resonance imaging and CT findings were compared to document the distribution of the injected preparation and identify effects on adjacent tissues. Percutaneous injection of the intervertebral disc was successful in delivering radiopaque gelified ethanol to the nucleus pulposus in all dogs. Leakage of the injected material into the vertebral canal was present in three dogs immediately following injection and in another additional dog at 1 year following injection. All dogs tolerated the injection well and had no clinical adverse reactions within the study period. Findings indicated that injection of the nucleus pulposus of healthy dogs was well tolerated, even in the presence of mild leakage of material from the intervertebral disc.